2003
DOI: 10.1636/s01-40
|View full text |Cite
|
Sign up to set email alerts
|

Web Orientation of the Banded Garden Spider Argiope Trifasciata (Araneae, Araneidae) in a California Coastal Population

Abstract: Magnetic heading (direction the spider's ventrum faced) and web inclination (degree of slant from the vertical) in Argiope trifasciata Forskal, a diurnal orb-weaving spider, were studied at a coastal site in southern California for nine weeks in fail 1999. Throughout the study, A. trifasciata largely occupied east-west oriented webs with their venters facing south and southwest. Mean magnetic heading was unaffected by ambient temperature extremes. Inclination levels varied from week to week over an approximate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…A sit-and-wait predator like Argiope (Olive 1982), which is permanently exposed to sun and desiccation stress (Tolbert 1979;Ramirez et al 2003), must rely on a variety of mechanisms to minimise water loss and efficient mechanisms to gain water. The spiders in our study were not water or food deprived, yet all spiders showed the same stereotypic behavioural elements of water search and drinking in the hub cover, suggesting that this web decoration might be of adaptive significance for A. bruennichi.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A sit-and-wait predator like Argiope (Olive 1982), which is permanently exposed to sun and desiccation stress (Tolbert 1979;Ramirez et al 2003), must rely on a variety of mechanisms to minimise water loss and efficient mechanisms to gain water. The spiders in our study were not water or food deprived, yet all spiders showed the same stereotypic behavioural elements of water search and drinking in the hub cover, suggesting that this web decoration might be of adaptive significance for A. bruennichi.…”
Section: Discussionmentioning
confidence: 99%
“…Several species of the araneid genus Argiope occupy dry habitats (Enders 1973(Enders , 1974Olive 1980;Edmunds 1986), making them vulnerable to water loss during dry seasons. The lack of protective retreats (Levi 1968;Scharff and Coddington 1997) further aggravates drystress situations (Ramirez et al 2003), compared with orb weaving species which can take cover in hideouts (Foelix 1996).…”
Section: Introductionmentioning
confidence: 99%
“…As prey abundance and richness increases in canopies of European black pine, Pinus nigra Arnold, so does the abundance, richness, and diversity of the associated spider community (Horváth et al 2005). Several web-weaving spider species, including those found in canopies of eastern hemlock T. canadensis (L.) Carriè re, orient their webs in a direction favorable for thermoregulation and prey capture, depending on microhabitat and abundance of prey (Biere and Uetz 1981, Caine and Hieber 1987, Bishop and Connolly 1992, Ramirez et al 2003, Justice et al 2005, Mallis and Rieske 2010.…”
mentioning
confidence: 99%
“…Spiders exhibit various behavioral ways to avoid web damages under windy conditions. For example, some orb-weaving spiders oriented their webs to parallel the direction of wind to minimize exposure area (Schoener and Toft 1983;Ramirez et al 2003). Araneus spiders reduce radii number, spiral length, and web area when they experience strong winds (Hieber 1984), and webs changed in this way are also stiffer (Vollrath et al 1997).…”
mentioning
confidence: 99%